A pilot study of factors associated with resilience to substance abuse in adolescent sons of alcoholic fathers. - Springer, S A; Gastfriend, D R (Journal of addictive diseases, 1995)
This pilot study evaluated the association between substance abuse outcome and putative protective factors in sons of alcoholic fathers. A battery of questionnaires was anonymously self-administered to 24 sons of alcoholic fathers ages 16-19 years to identify relationships between alcohol and/or drug abuse and factors hypothesized to be related to parental alcoholism. Of the 24 subjects, 13 were categorized through self-identification and self-report screening measures as having alcohol and/or drug problems and 11 were categorized as not having substance abuse problems. Boys without substance problems: (1) had significantly higher maternal occupational status (p = .01); (2) experienced more good life events (p < .001), and (3) had a more internally oriented locus of control (p < .001). Good events and internal locus of control were highly correlated with each other (r = .620, p < .01). The fact that these preliminary findings are consistent with other literature despite marked methodologic and sample differences indicates that these putative components of resilience are robust and deserve further study towards improved substance abuse prevention in those at high risk.
Keywords: Adolescent; Adolescent Behavior; Adult; Alcoholism; Child; Fathers; Humans; Internal-External Control; Life Change Events; Male; Mental Disorders; Mothers; Pilot Projects; Psychiatric Status Rating Scales; Questionnaires; Self-Assessment; Substance-Related Disorders